From silks to sands: a wellness journey through aerial yoga, pilates & seaside serenity / Nurul Asyikin Md Zaki - Md Zaki, Nurul Asyikin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
I remember the first time I caught a glimpse of an Instagram influencer effortlessly suspended in the air, wrapped in a silk hammock, gracefully transitioning into a pose. The spectacle of aerial yoga left me in awe. Meanwhile, the elegance of Pilates, with its emphasis on posture and core strength, had always intrigued me. It was high time I embarked on my personal fitness journey, taking the leap from ground to sky. Our world has seen a surge in unique fitness routines, each promising transformative result. Aerial yoga, an ethereal blend of traditional yoga and aerial acrobatics, and Pilates, a discipline focusing on alignment and core strength, have made their mark in the contemporary wellness landscape. "It's not just about fitness; it's a dance between discipline and strength," quotes Reiko, an aerial yoga instructor I had the pleasure to learn from. Similarly, Joan, my Pilates trainer, believes, "Pilates isn’t just exercise; it's a way of aligning your body and soul."